Glomus Tumor of the Finger Diagnosed on Bone Scintigraphy - Lombardi, Alecio F.; Martinez, Felipe; Long, Jeremiah R. (World Journal of Nuclear Medicine, 2025)
A 60-year-old woman with chronic pain in the left long finger, occasionally involving the ring finger and intermittently extending to the hand, wrist, and distal forearm, was referred for radiographs and a triple-phase technetium-99m methylene diphosphonate bone scintigraphy to evaluate for possible complex regional pain syndrome. Initial radiographs were normal. A three-phase bone scan revealed focal radiotracer uptake at the distal aspect of the long finger during the blood pool phase only, with normal blood flow and delayed phases, suggesting a hypervascular soft tissue tumor. Follow-up magnetic resonance imaging showed a hypervascular nodule in the nail bed of the long finger. The lesion was surgically resected, and pathology results confirmed the diagnosis of a glomus tumor.
Keywords: glomus tumor; finger; bone scintigraphy; MRI